Upaya Guru Dalam Menanamkan Nilai-Nilai Agama Pada Siswa Taman Pendidikan Al Qur’an Al-Hikmah Salatiga - Fahmi eko saputro (At-Ta'lim : Media Informasi Pendidikan Islam, 2020)
Abstract: Teachers' Efforts in Instilling Religious Values in the Park Students Al Qur'an Education Al-Hikmah SalatigaEducation, which is one of the important factors in the development of the nation and state, especially for realizing the development of the Indonesian human being completely focused on the mental development of the younger generation so that it is expected to become the next generation of the nation who is devout, virtuous, skilled, independent and responsible in accordance with the objectives of national education , and also the teacher's efforts in making the nation's children have personalities who are devout to God Almighty. The purpose of this study was to determine the teacher's efforts to instill religious values in TPQ Al-Hikmah students through Aqidah education, worship education, and moral education. This research method is descriptive qualitative. Data collection techniques are interviews, observation and documentation. The data analysis technique used several stages of identification. The results of this study indicate that the teacher's efforts to instill religious values in the process are through education of aqidah, namely introducing God, worship carrying out God's commands and staying away from His prohibitions, and Morals, namely establishing good relationships between humans.